Prototipagem : uma abordagem ao processo de desenvolvimento de um produto - Palhais, Catarina, 1992- (2017)
The design has gradually been seeking new solutions to ensure greater effectiveness of the emerging market response. The use of prototyping, real and virtual, through manual prototyping to rapid prototyping, are an integral part of a product development process. A new phase emerged with the development of virtual designed products, allowing more formal complexity in a short time. Based on these solutions, it is up to designers to apply the tools they have in order to reduce production time and project costs, achieving better results and facilitating communication with customers and with the user. This paper aims to reflect on the prototype construction methods and their application in various segments that have evolved significantly. Prototyping is considered as an important tool for the Product Development Process. The purpose of designing products is to satisfy customer needs and improve competitiveness of companies in the market. The prototyping assists the process of product development, since it enables the simulation of the full scale product, allowing the identification of design errors. In this sense are revealed concepts such as the need to provide the actual behavior of your project, the use of prototyping, manual processes, digital and rapid prototyping. It was carried out a case study of the workshops and Projectlabb the Faculty of Fine Arts UL, which was intended to ascertain the impact on the development of a product, by working in parallel manual processes and rapid prototyping for the development of final prototypes